The effect of vacuum pressure on the flammability limits of liquefied petroleum gas (LPG) - Norazma, Mukhtar (2010)
The Liquefied Petroleum Gas (LPG) is a flammable mixture of hydrocarbon gases. In transportation or handling the LPG gases, it is very important to know the flammability limits and the pressure of the gas to avoid any accident or explosion occurred. The pressure of LPG takes part in the flammability limits either Upper Flammability Limit (UFL) or Lower Flammability Limit (LFL). So, the aims of this research are to investigate the effect of vacuum pressure on the flammability limits of LPG/air. The experiments are performed in a 20 L spherical explosion vessel. The mixtures are ignited using spark permanent wire that place at the centre of the vessel. The pressures are used starting from 0.96 bar up to 1.0 bar. The pressure-time variations during explosions of LPG/air mixtures in explosion vessel are recorded. The explosion pressure data is used to determine the flammability limits which flame propagation is occurred if explosion pressure greater than 0.96 bar. In this experiment, the result shows the LFL is decrease when the pressure decreasing but, UFL is increasing with the increasing of pressure. The LFL for 0.98 bar is 2 volume % of LPG and for 0.96 bar is 1 volume % of LPG. The UFL for 0.98 bar and 0.96 bar are the same which is 8 volume % of LPG. But the Pm for UFL for 0.98 bar is 0.7 bar and Pm for UFL for 0.96 bar is 0.9 bar.